Horizontal and vertical spillovers in wage bargaining: A theoretical framework and experimental evidence. (February 2018) - Lehr, Alex; Vyrastekova, Jana; Akkerman, Agnes; Torenvlied, René
Conflict in wage bargaining is affected by information about other bargaining units and information about the past of the bargaining unit. We develop a theoretical framework for such spillovers and detail four distinct mechanisms. Rational learning and social comparisons are reviewed as mechanisms for the influence of information about other bargaining units, and reputation and expectation effects are reviewed as mechanisms for the influence of information about the past of the bargaining unit. Building upon a previous experimental study, we implement an unstructured, time-limited, two-person bargaining game with asymmetric information and investigate the impact of reputation and expectation effects. The experimental treatments vary with respect to spillover-inducing information available to the participants. The results suggest that reputation effects decrease conflict, whereas expectation effects tend to increase conflict. Moreover, reputation effects diminish the influence of social comparisons but can augment the effects of rational learning.